Post-conflict microfinance: assessment and policy notes for Iraq - Sameeksha Desai (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
This paper explores the potential of microfinance in post-conflict economies, and speci-fically examines policy considerations for the case of Iraq. It presents important condi-tions of the post-conflict economy, and examines three critical requirements for suc-cessful microfinance operations, as outlined by the Microenterprises Best Practices Project. Political stability, economic demand and population stability are evaluated in the case of Iraq. Several other considerations are also addressed, including matters of sca-le, government mechanisms and support, and gender and religious contexts.
Keywords: O1; O5; P2; 330; microfinance; Iraq; postconflict; political stability; population stability; Mikrofinanzierung; Kriegsschaden; Politische Stabilität; Bevölkerungsentwicklung; Irak